Establishment of a Stable β-Casein Protein-Secreted Laoshan Dairy Goat Mammary Epithelial Cell Line - Zhang, Hongyan; Liu, Tianzhen; Li, Boyu; Zhang, Kang; Wang, Dong; Liu, Ying; Ge, Lijiang; Jiang, Yunliang; Su, Feng (Frontiers in Veterinary Science, 2020)
Mammary epithelial cells are widely used as models in mastitis research and as tools for mammalian bioreactors; however, the short lifespan of these cells limits their utility. Several mammal epithelial cell line models have been established; however, the secretion capacity and the bacterial sensitivity of these lines have not been effectively evaluated. In this study, a stable immortalized goat mammary epithelial cell (GMEC) line was constructed by transfection with the SV40 gene. The monoclonal cells were then passaged through more than 50 generations after puromycin selection. The GMEC line was evaluated by reverse transcriptase polymerase chain reaction, the cell cycle, karyotype analysis, detection of apoptosis, Western blotting, and β-casein (CSN2) inducible assays. The GMEC line had a strong proliferation capacity relative to the primary GMECs. GMECs had the same karyotype as the primary cells. The GMEC lines maintained basic biological properties and had estrogen, prolactin and progesterone receptors as same the primary cells. Additionally, the cells and the cell line could synthesize and secrete β-casein proteins. Finally, the rate of apoptosis of the transfected cells suggested that the cell line could provide a useful tool for signal research and mammary gland bioreactors.